URGENSI LITERASI SAINS SISWA SD DALAM MENINGKATKAN RASA CINTA LINGKUNGAN: STUDI KASUS - Indriyani, Santi; Joko Suprapmanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the importance of scientific literacy in cultivating an environmental awareness and care among elementary school students. Although various environmental programs have been implemented in schools, initial observations indicate that student behaviors in maintaining the environment are often motivated by external instructions rather than grounded in a strong scientific understanding. Employing a descriptive qualitative approach, this study collected data through online documentation and semi-structured interviews involving representatives from the Sub-district Environmental Agency, school principals, classroom teachers, and science subject teachers. The results reveal that students’ comprehension of scientific concepts related to environmental issues is essential in fostering both awareness and intrinsic motivation to protect and preserve nature. A lack of scientific literacy tends to reduce environmental initiatives into repetitive routines that lack meaningful internalization. Therefore, integrating scientific literacy into the curriculum and learning activities is considered crucial in shaping a generation that is not only environmentally conscious but also scientifically informed and responsible.